2013
DOI: 10.1088/0004-637x/774/2/97
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Rich Molecular Chains in Protoplanetary and Planetary Atmospheres: Quantum Mechanisms and Electron Attachment Rates for Anion Formation

Abstract: The elementary mechanisms through which molecular polyynes could form stable negative ions after interacting with free electrons in planetary atmospheres (e.g., Titan's) are analyzed using quantum scattering calculations and quantum structure methods. The case of radical species and of nonpolar partners are analyzed via specific examples for both the C n H and HC n H series, with n values from 4 to 12. We show that attachment processes to polar radicals are dominating the anionic production and that the mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 33 publications
(50 reference statements)
7
59
5
Order By: Relevance
“…The discovery of several carbon chain anions, C n N − (n = 1, 3, 5) and C n H − (n = 4,6,8) in the ISM has prompted a discussion about mechanism of their formation in the ISM [4][5][6][7]. Well before their discovery, the formation of molecular anions in the ISM was theorized by Herbst [8], who suggested that the anions could be formed in the ISM by radiative electronic attachment (REA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of several carbon chain anions, C n N − (n = 1, 3, 5) and C n H − (n = 4,6,8) in the ISM has prompted a discussion about mechanism of their formation in the ISM [4][5][6][7]. Well before their discovery, the formation of molecular anions in the ISM was theorized by Herbst [8], who suggested that the anions could be formed in the ISM by radiative electronic attachment (REA).…”
mentioning
confidence: 99%
“…However, for all carbon chain anions observed in the ISM the potential energy surfaces of the neutral molecule and the anion are almost parallel to each other, which implies that the electron capture cross section is small. One possibility in the process of REA that was not considered in this approach, is the role of weakly-bound dipole states of molecules with large dipole moments, such as C 5 N. Recently, it was suggested [5][6][7] that the weakly-bound dipole states might enhance the REA cross section, although no quantitative predictions have yet been made. A dipole state with a rotationally or vibrationally excited molecular core appears as a resonance in the electronic continuum spectrum and, therefore, can in principle enhance the REA cross section, at least, in some energy domains.…”
mentioning
confidence: 99%
“…This would then favor the direct REA decay into a dipole-type bound state because of the strong spatial similarities between the two extra-electron wave functions. 27 The latter anion could in turn either undergo an internal vibrational redistribution type of mechanism and form a stable valence bound anion or suffer the extra electron loss via autodetachment.…”
Section: Present Conclusionmentioning
confidence: 99%
“…Moreover, as already discussed at length in section III B, the threshold behavior in the photodetachment cross section of C 6 H − is expected to be different than the usual Wigner threshold law (see Eq. (14)). Indeed, our calculations clearly demonstrate that several low-energy partial waves transition dipole moments, shown in Fig.…”
Section: Photodetachment Of C6h −mentioning
confidence: 99%
“…During the last decade, numerous astrophysical observations [1][2][3][4][5][6][7] have confirmed the long-standing prediction by Herbst [8] on the existence of negatively charged ions in the interstellar medium (ISM). These recent discoveries have triggered a revived interest in understanding the general formation and destruction mechanisms of these exotic species [9][10][11][12][13][14]. The main destruction pathways of anions in astronomical objects exposed to ultraviolet radiations is the detachment of a bound electron following the absorption of a photon with energy ω > EA, where EA is the electron affinity of the A radical…”
Section: Introductionmentioning
confidence: 99%